IMPLIKATUR PERCAKAPAN ANAK USIA 7 TAHUN DALAM KEGIATAN ANAK DAN ORANG TUA PADA KONTAK INTERPERSONAL - Piani, Ririn Tria; Sumarti, Sumarti; Samhati, Siti; Eko Rusminto, Nurlaksana; Widodo, Mulyanto (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
Conversational implicatures are hidden expressions of intent that can occur in various speech situations, one of which is in interpersonal contact between children and parents. This research aims to describe the timing of the use of conversational implicatures in children's communication with their parents when they occur. This type of research is qualitative research with research data in the form of words in conversational speech which are indicated to contain implicatures in them. Data collection was carried out by observation using listening techniques and note-taking techniques. The approach used is a pragmatic approach by utilizing implicature theory. The results of the research show that speech implicatures in interpersonal contact between children and parents occur when going to school and going to the Al-Quran Education Park. Pragmatic speech in interpersonal contact between parents and their children contains many conversational implicatures which are directive in nature, namely commands and requests.